Approaches to Slavic interaction - Thielemann, Nadine; Kosta, P. (Peter) (Dialogue studies ;)
This article proposes an interactional approach to the question of Russian language maintenance through the activity of bedtime story-reading in Russian-French bilingual families in French speaking Switzerland. Reading stories appears to be a language maintenance strategy commonly employed by the Russian speaking parent. The ritual and recreational moment of story-reading therefore becomes an opportunity for language learning. Drawing upon a language socialization perspective, this paper proposes an interactional analysis of the language use in the activity of story-reading. It shows how the l.